2006
DOI: 10.1523/jneurosci.1535-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Categorization and Perceptual Learning in Patients with Hippocampal Damage

Abstract: Prevailing theory holds that the medial temporal lobe (MTL) subserves declarative memory exclusively, whereas nondeclarative memory is independent of this brain region. Recent studies in patients with amnesia, however, have shown that performance on declarative memory tasks may not always be dependent on a single MTL memory system, instead highlighting the critical role of anatomically distinct structures in processing different stimulus types. In particular, the hippocampus has been implicated in spatial memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 62 publications
12
97
1
Order By: Relevance
“…Our view is that perceptual learning can indeed occur in PRh. Evidence suggests it also does in the hippocampus (Graham et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our view is that perceptual learning can indeed occur in PRh. Evidence suggests it also does in the hippocampus (Graham et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During perception, the hippocampus binds together visual elements of an image (Olsen et al, 2012;Warren et al, 2012;Zeidman et al, 2015), which is especially important for scene stimuli (Lee et al, 2005a,b;Graham et al, 2006;Hodgetts et al, 2016) and then stores this representation into long-term memory (Ryan and Cohen, 2004). As we become familiar with an environment, the hippocampus builds a map of the spatial relationships between visual landmarks, which is critical for navigation (Morgan et al, 2011).…”
Section: The Memory and Navigation Networkmentioning
confidence: 99%
“…Recent findings in monkeys and in humans with perirhinal cortex lesions have been taken to indicate that perirhinal cortex is needed for visual discrimination tasks when the test items have a high degree of feature ambiguity (Bussey et al 2002;Barense et al 2005Barense et al , 2007Lee et al 2005a,b; but see Clark et al 2011). It has also been suggested that the hippocampus is needed when spatial processing is required, for example, in visual discriminations involving scenes (Lee et al 2005a;Graham et al 2006). The challenge is to decide whether impaired performance reflects impaired perception or impaired memory (for reviews of this growing literature, see Hampton 2005;Buckley and Gaffan 2006;Baxter 2009;Suzuki 2009;Graham et al 2010).…”
Section: Visual Discrimination Tasksmentioning
confidence: 99%
“…In some studies in monkeys and also in humans (e.g., Barense et al 2005;Graham et al 2006), discrimination learning involved the same stimulus materials over multiple trials. In these cases, impaired performance could reflect a deficit, not in perception, but in associative learning or long-term memory for the repeated material (Hampton 2005;Suzuki 2009;Wixted and Squire 2011).…”
Section: Visual Discrimination Tasksmentioning
confidence: 99%